SETTLEMENT OF STATE ADMINISTRATIVE DISPUTES - Yudith Bana (Faculty of Law, Khairun University, 2023)
Indonesia is a country of law as stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. In line with these provisions, it provides an understanding that all government actions must be based on law. The law here is a guideline and limiter for the implementation of authority carried out by the government. This is intended so that the government is not arbitrary in its actions. The government's authority is focused on implementing executive power at both the central and regional levels. As this has been shared in Baron de Montesquie's theory of the Separation of Powers, which requires that executive power is government power. This research uses a normative method with a statutory approach (statue approach) and a conceptual approach (conceptual statue), the source of legal materials is obtained from primary legal materials, secondary legal materials, tertiary legal materials, the technique of collecting legal materials in this research is carried out through a card system. (card system). The analysis technique used in this research is descriptive analytic analysis technique. Apart from that, we also use evaluation techniques, which are carried out by providing an assessment to find out whether a view, proposition, norm formulation statement, and decision stated in legal materials are correct or not, and the last is the argumentation technique. This argumentation technique cannot be separated from the evaluation technique. Because the assessment must be based on reasons that are in accordance with legal logic.